Extended screening: service delivered by a psychological clinic - Herzberg, Eliana; Chammas, Débora (Paidéia (Ribeirão Preto), 2009)
This article aimed to present and discuss a psychological screening process carried out at a psychological outpatient clinic in São Paulo-SP. The extended screening service based on a psychoanalytical reference and opposed to the traditional one, could be carried out in up to six interviews. Ten participants who had not managed to be included in the weekly screening were studied. The analysis included adherence, manifest versus latent complaints, process development, expectations regarding attendance and referrals. The conclusion is that this form of attending clients is viable and present advantages in a reality devoid of health services and resources.